Role of Poultry Meat in Sporadic Campylobacter Infections in Bosnia and Herzegovina: Laboratory-based Study - Uzunović-Kamberović, Selma (Croatian Medical Schools, 2007)
AIM: To investigate genetic diversity and specificity of Campylobacter jejuni and Campylobacter coli strains isolated from humans, retail poultry meat, and live farm chickens in Zenica-Doboj Canton, Bosnia and Herzegovina, and identify the role of poultry meat in sporadic Campylobacter infections. METHODS: We determined the type of Campylobacter species using standard microbiological methods and multiplex polymerase chain reaction (PCR), and performed pulsed field gel-electrophoresis (PFGE) and restriction fragment length polymorphism (RFLP) typing of the flaA gene to investigate genetic diversity among the isolates. RESULTS: We isolated C jejuni and C coli from 75 (5.2%) of 1453 samples of consecutive outpatients with sporadic diarrhea; from 51 (34.7%) of 147 samples of poultry meat; and from 15 out of 23 farm chicken samples. The proportion of C coli found among human (30.1%), poultry meat (56.9%), and farm chicken isolates (53.3%), was greater than the proportion of C jejuni. Fourteen and 24 PFGE genotypes were identified among 20 C coli and 37 C jejuni isolates, respectively. Identical PFGE genotypes were found in two cases of human and poultry meat isolates and two cases of poultry meat and farm chicken isolates. CONCLUSION: Only a minority of human Campylobacter isolates shared identical PFGE type with poultry meat isolates. Although poultry is the source of a certain number of human infections, there may be other more important sources. Further research is required to identify the environmental reservoir of Campylobacter spp responsible for causing human disease and the reason for the high prevalence of C coli human infections in this region.